2021
DOI: 10.1016/j.bj.2021.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The genetic landscape of the FAS pathway deficiencies

Abstract: Dysfunction of the FAS-FASLG pathway causes a lymphoproliferative disorder with autoimmunity called Autoimmune lymphoproliferative syndrome (ALPS) mainly caused by FAS mutations. The goal of this review is to describe the genetic bases of the autoimmune lymphoproliferative syndrome and to underline their genetic complexity with the contribution of both germline and somatic events accounting for the variable clinical penetrance of the FAS mutations. Starting from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…They also have a closer look at inherited non-FAS mutations that play a part in ALPS. Finally, they suggest that a second event next to any mutation affecting the FAS induced apoptosis might be involved in ALPS onset [ 4 ].…”
Section: James Bond: “When I Kill It Is On Specific Orders”mentioning
confidence: 99%
“…They also have a closer look at inherited non-FAS mutations that play a part in ALPS. Finally, they suggest that a second event next to any mutation affecting the FAS induced apoptosis might be involved in ALPS onset [ 4 ].…”
Section: James Bond: “When I Kill It Is On Specific Orders”mentioning
confidence: 99%
“…Upon T lymphocyte activation, an expression of Fas ligand (FASL) and its interaction with FAS receptors is triggered, leading subsequently to binding of FAS-associated protein with death domain (FADD). FADD then recruits pro-caspases 8 and 10 to engender the death-inducing signaling complex (DISC) and generates terminal caspase activation leading to cell death (1)(2)(3). This tightly regulated system of controlling lymphocyte stimulation plays a critical role in immune homeostasis thereby preventing an expansion of autoreactive T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune lymphoproliferative syndrome (ALPS) also known as Canale-Smith syndrome is a disorder of the extrinsic first apoptosis signal (FAS)-mediated pathway of lymphocyte apoptosis characterized by marked genetic and clinical heterogeneity ( 1 , 2 ). The hallmarks of the disease are childhood-onset chronic non-malignant, non-infectious lymphoproliferation manifesting as lymphadenopathy and/or splenomegaly, autoimmune cytopenia, and polyclonal IgG hypergammaglobulinemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first review article, Dr. Magerus and her colleagues analyze mutations affecting the FAS pathway associated with ALPS diagnosed in 130 patients of a French cohort, in addition to the mutations described in the literature [ 3 ]. In the first part of this review, the Fas/Faslg autosomal recessive mutations identified in mice are compared to the FAS/FASLG mutations in humans.…”
mentioning
confidence: 99%